Ikhtiar Guru Fiqih dalam Meningkatkan Ibadah Siswa Kelas VIII di Madrasah Tsanawiyah Negeri 5 Jember - Moh. Anwar (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2020)
This study purposes to find out awareness of worship, especially the Dhuhur and Dhuha prayers in congregation of students and the efforts of fiqh teachers in increasing this consciousness and the factors influence it. The method of this study used a qualitative approach. The data analysis used interactive analysis from Milles & Huberman and Saldana. Data collection used interviews, observation and documentation. The result of this study showed some points: initially, students' awareness of worship in worshipping, especially Dhuhur and Duha prayers in congregation, is partly lacking, this is because: there is a broken home family, there is no role model as parents and the playing environment is less supportive. Second, fiqh teacher’s ikhtiar in raising awareness of wrship, especially Dhuhur and Duha prayers in congregation, through: (a) provide insight into prayer; (b) nurturing motivation; (c) there is a shift team that supervises prayer; and (d) holding religious activities filled with praxis. Thirdly, the substantiating factr: (a) facilities and infrastructure; (b) self-awareness; (c) motivation from teachers and remind students who violate. As for the inhibiting factors: (a) the environment at home, such as the lack of attention from parents, (b) friends who drop out, (c) basic students from elementary school education so they absence religious insight, especially prayer.